Sleep Quality Partially Mediate the Relationship Between Depressive Symptoms and Cognitive Function in Older Chinese: A Longitudinal Study Across 10 Years - Guo H; Zhang Y; Wang Z; Shen H (Psychology Research and Behavior Management, 2022)
Huan Guo,1,2 Yancui Zhang,3 Zhendong Wang,4 Heyong Shen2 1School of Human Resources, Guangdong University of Finance & Economics, Guangzhou, People’s Republic of China; 2Institute of Analytical Psychology, City University of Macau, Macau, People’s Republic of China; 3Postdoctoral Research Center of School of Psychology, Nanjing Normal University, Nanjing, People’s Republic of China; 4School of Basic Medical Sciences, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Heyong Shen, Email shenheyong2018@hotmail.comObjective: This study aimed to examine the relationship between cognitive function and depressive symptoms and to explore the mediating role of sleep quality in the cognition-depression relationship in Chinese older adults (OAs).Methods: Data came from a nationally representative sample of 16,209 Chinese OAs (aged 65+) from 2008, 2011, 2014, and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). A random intercept cross-lagged panel model (RI-CLPM) combined with mediation analysis was adopted to determine the relationship between cognitive function and depressive symptoms and the mediating effect of sleep quality on the ascertained cognition–depression relationship.Results: Poorer cognitive function at prior assessment points were significantly associated with severe depressive symptoms at subsequent assessments, and vice versa. Sleep quality partially mediated the prospective relationship of cognition on depressive symptoms, which accounted for 3.92% of the total effect of cognition on depression.Discussion: Cognitive decline may predict subsequent depressive symptoms, and vice versa. The impact of cognition on depression is partially explained by its influence on sleep quality. Multidisciplinary interventions aimed at reducing depression and cognitive decline per se as well as improving sleep quality would be beneficial for emotional well-being and cognitive health in OAs.Keywords: cognitive function, depressive symptoms, sleep quality, random intercept cross-lagged panel model, mediation, Chinese older adults